Combination therapy of the plaque form of Weber–Christian idiopathic panniculitis - O. N. Egorova; B. S. Belov; S. G. Radenska-Lopovok; Ye. G. Sazhina (Klinicist)
Panniculitides are a group of heterogenic inflammatory diseases that involve the subcutaneous fat. Treatment for panniculitides, idiopathic ones in particular, has not been conclusively developed and is generally performed empirically. The paper describes a case successfully treated with glucocorticosteroids in combination with azathioprine for the plaque form of Weber–Christian panniculitis.